The Analysis of Household Waste Management Based on Integrated Sustainable Waste Management in Sungailiat City - Widya Handini (Program Pascasarjana Universitas Sriwijaya, 2022)
Statistics Indonesia (BPS) data in 2016 states that waste generation in Indonesia reached 65 million tons/year. It is predicted that in 2025, the number of waste generation in urban areas will increase to 2.2 billion tons/year of 4.3 billion of population in Indonesia. In Bangka Regency, there are several issues related to waste along with regional development and increasing population, which is the increasing of waste generation every year. The Environmental Department of Bangka Regency since 2018 had pursued a target of 30% waste processing and 70% waste management by 2025 according to the National Policy and Strategy program. Therefore, it is important to carry out a review and analysis of waste management in this place to achieve the target of reducing and handling waste in waste problems solving. If waste management has not done optimally, it will increase the air and water pollution which disrupt human life. In this paper, the concept is Integrated Sustainable Waste Management (ISWM). The method used is a qualitative analysis method by interview, observation, and documentation. The results showed several aspec in line with the ISWM, but other things has to improve in term of technical and non-technical aspects.